Study and monitoring of the anaerobic digestion process in batch regime of Arundo donax L., including scale-up evaluation (Semiárida, 2025)
The utilization of perennial energy crops such as Arundo donax L., with high productivity and low input requirements, has attracted interest as a sustainable alternative for bioenergy generation. In this context, the treatment of biomass through anaerobic digestion has increased, driven by the assessment of the main benefits associated with this technology as an effective strategy for converting organic matter into energy in the form of biogas. This study evaluated the anaerobic digestion of Arundo donax L. in a temperature-controlled batch reactor with a working volume of 7 L, operated under mesophilic conditions and using sludge from a wastewater treatment plant as inoculum. The process was assessed by monitoring physicochemical parameters in the reactor and quantifying biomethane production. In parallel, a standardized assay was performed to determine the Biomethane Potential (BMP) of the biomass. The results showed a BMP of 220.07 ± 2.7 mL CH₄ g VS-1, while the specific biomethane production in the batch reactor reached 131.60 mL CH₄ g VS-1, representing a 40 % reduction attributable to process scaling. This discrepancy may be associated with factors such as mixing efficiency, mass transfer limitations, or the actual biodegradability of the biomass under operational conditions. The monitored physicochemical parameters confirmed the stability of the process, indicating that the system operated under controlled conditions without signs of inhibition.
Keywords: Biomethane Potential; Lab-scale Reactor; Giant Reed